2011
DOI: 10.2147/ijgm.s23206
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of enhanced risk of retinal neovascularization in repeated blood donors: blood donation and retinal alteration

Abstract: Repeated blood donors manifest clinical, subclinical, and biochemical signs of iron deficiency anemia, have significantly higher erythropoietin and vascular endothelial growth factor (VEGF) concentrations, and decreased tissue oxygen saturation, oxygenated tissue hemoglobin, and regional cerebral oxygen saturation. Erythropoietin and VEGF are potent retinal angiogenic factors which may initiate and promote the retinal angiogenesis process independently or simultaneously. Increases in circulating levels of eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Most of the recently published articles benefit from elegant and sophisticated methodology. 4 However, although anemia is causally related to angiogenesis and neovas-cularization, 5 especially in ocular situations, 6 neither the published nonrandomized clinical trials nor the registered nonrandomized clinical trials have reported the anemia status as inclusion or exclusion criteria in their design. The main methodological issue here is that whether the iron-deficiency status in enrolled patients confound the efficacy of angiogenesis inhibitors, since a low hemoglobin level is associated with increased serum levels of vascular endothelial growth factor (VEGF) and it has been suggested that anemia might increase the progression of angiogenesis.…”
Section: Anemia and Angiogenesis Inhibitorsmentioning
confidence: 99%
“…Most of the recently published articles benefit from elegant and sophisticated methodology. 4 However, although anemia is causally related to angiogenesis and neovas-cularization, 5 especially in ocular situations, 6 neither the published nonrandomized clinical trials nor the registered nonrandomized clinical trials have reported the anemia status as inclusion or exclusion criteria in their design. The main methodological issue here is that whether the iron-deficiency status in enrolled patients confound the efficacy of angiogenesis inhibitors, since a low hemoglobin level is associated with increased serum levels of vascular endothelial growth factor (VEGF) and it has been suggested that anemia might increase the progression of angiogenesis.…”
Section: Anemia and Angiogenesis Inhibitorsmentioning
confidence: 99%
“…But hyperprolactinemia, particularly in women and also in men, has been associated to treatment with both typical and atypical antipsychotics such as risperidone and probably to others [1][2][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%